Characteristic in Poulenc’s Sonata for Piano Four Hands, FP8 - Yommana, Machaporn; Pongsarayuth, Sasi (Rangsit Music Journal, 2021)
Poulenc’s Sonata for Piano Four Hands is one of the significance piece of compositions for piano duet in the twentieth century. An archive in itself, a unique representation of the musical characteristic of its time. A piece of music where the composer put his attention down the very minute details, even the posture and movement of the performers were exquisitely choreographed which distinguished this piece from other piano four hands compositions. This research is intended to provide an in-depth overview of the characteristics found in this sonata as well as typical characteristics of piano duet previous to this composition. The results of the research revealed that the special feature of the song is the development and adaptation of techniques for piano four hands which originally only meant to achieve a more extensive musical details and harmony unable to accomplish by a piano solo alone. This exquisite composition of Poulenc corporates much more than a musical notation but rather a delicate piece of composition where two performers are choreographed to connect to each other in order to indulge and express this fine composition.